RBF Nerve Network Tuning PD Control Scheme for Tele-operation Robot Servo System - Guang Wen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In the bilateral hydraulic servo control system of a construction tele-robot with in-situ force sensing, the p-f type force feedback architecture is liable to result in an impact on the operator hand, and its high amplitude will cause the control unstable. In order to solve this problem an improved force feedback control method with the feature of a T-S fuzzy feedback coefficient, which could be modified online nonlinearly and continuously, is proposed. And a RBF-PID force controller is also designed, and formed a bilateral hydraulic servo control system. The experimental results indicate that the new improved control method reduced the impact of the feedback force, the compliance and transparency of the tele-operation of construction tele-robot system are enhanced. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2731